Efficiency and possibilities for Arabica coffee-banana management systems switching in the Mt. Elgon landscape of Uganda - Sebatta, C.; Mugisha, J.; Bagamba, F.; Nuppenau, E.A.; Domptail, S.E.; Ijala, A.; Karungi, J. (African Crop Science Journal, 2020)
Sustainably intensifying rural agricultural systems is now a development goal that has gained momentum in the recent decades due to a rapidly growing population and feeds directly into the Sustainable Development Goals of ending poverty and hunger. By 2050, the world will be inhabited by 10 billion people, 68% of whom will be city dwellers which will pose serious food and livelihoods security threats to millions of people, especially in Sub-Saharan Africa. The objective of this study was to analyse technical efficiency of four production systems in Arabica coffee-banana farming system of the Mt. Elgon in Uganda and assesses possibilities for switching from one system to another. The study was motivated by the notion that smallholder farmers do not easily adopt new systems because of opportunity costs related to input substitution, input and/or efficiency reduction and systems redesigning. We estimated a production function to measure technical efficiency and ordered the intensification pathways to create a Technical Efficiency (TE) gradient. An ordered logit model was then estimated to determine the factors influencing farmers to switch among systems, by adopting one or more following a TE gradient. Results showed that farmers produced 50% of the maximum possible Arabica coffee output, indicating huge gaps between actual and potential yields. Use of fertiliser for the lowest efficiency. Low-input-low-output pathway and improved coffee genotypes, manure and labour intensification for the higher technical efficiency clusters such as conventional and mild agroecological would also significantly increase the chances of switching from low to highly efficient and sustainable Arabica coffee production systems in the Mt. Elgon watershed of Uganda.
Keywords: Mountain watershed, Ordered logit, production function